DILEMA GEN Z DI DUNIA KERJA : BURNOUT ATAU QUIET QUITTING? - Indah Rahayu; Fariha Azzahra; Dita Prameswari; Dinda Putri Ramadhani; Adela Eka Ayu Trisiana (Jurnal Ekonomi dan Bisnis, 2025)
The phenomenon of quiet quitting is increasingly prevalent among Generation Z, which is a condition when employees only carry out minimum tasks without emotional involvement in work. One of the factors that influences this behavior is burnout. This study aims to analyze the effect of burnout on quiet quitting with work engagement as a moderating variable in Generation Z employees. This study uses a quantitative approach through a survey of 90 Generation Z  respondents in Grobogan Regency with a purposive sampling technique. Data analysis was carried out using Structural Equation Modeling (SEM) with the help of SmartPLS version 4.0. The results of the study showed that burnout had a positive and significant effect on quiet quitting, and a negative and significant effect on work engagement. Meanwhile, work engagement had a significant negative effect on quiet quitting, and significantly mediated the relationship between burnout and quiet quitting. The uniqueness of this study lies in the discovery of emotional exhaustion as the most dominant indicator of burnout and emotional disengagementas the highest indicator of quiet quitting. In addition, dedication as the main dimension of work engagement has been shown to be able to weaken the effect of burnout on quiet quitting. These findings provide a practical contribution for organizations to suppress quiet quitting behavior by strengthening employee work engagement.